Immune Checkpoint Inhibitors Plus Single-Agent Chemotherapy for Advanced Non-Small-Cell Lung Cancer After Resistance to EGFR-TKI - Deng, Haiyi; Lin, Xinqing; Xie, Xiaohong; Yang, Yilin; Wang, Liqiang; Wu, Jianhui; Liu, Ming; Xie, Zhanhong; Qin, Yinyin; Zhou, Chengzhi (Frontiers in Oncology, 2021)
Purpose: Platinum-based chemotherapy remains the classic treatment option for patients with advanced non-small-cell lung cancer (NSCLC) who progress while receiving treatment with epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs). In this study, we analyzed real-world outcomes of treatment with immune checkpoint inhibitors (ICIs) combined with platinum-free chemotherapy in patients with NSCLC after developing resistance to EGFR-TKIs. Materials and Methods: This retrospective study included patients with mutation-positive NSCLC after developing resistance to EGFR-TKIs. Patients who received chemotherapy alone plus ICIs with or without anti-angiogenic drugs between February 2019 and August 2020 were enrolled. Clinical characteristics, EGFR mutation status, response to ICIs, and adverse events (AEs) were retrospectively analyzed. Results: Eight patients were eligible and included in the analysis. The median age was 66 years, and 75% of the patients underwent at least two previous treatments. The overall response and disease control rates were 50% and 100%, respectively. At the time of survival analysis, the median progression-free survival was 6.5 months (95% confidence interval: 6.1–7.0). AEs of grades ≥3 were observed in two patients (25%) and were not immune-related; there was no discontinuation of ICIs related to the occurrence of severe AEs. Conclusion: ICIs plus platinum-free, single-agent chemotherapy provides promising progression-free survival and overall response rate benefit, along with a low rate of severe AEs in patients with EGFR-TKI-resistant advanced NSCLC.